EU emissions trading initiation, decision-making and implementation - Skjaerseth, Jon Birger; Wettestad, Jorgen (Ashgate Pub., 2008)
The EU Emissions trading scheme has been characterized as one of the most far-reaching and radical environmental policies. This work deals with EU's approach to environmental regulation that has the potential to change international strategies for environmental protection.